Characterization of AAV-mediated dorsal root ganglionopathy - Nicholas Buss; Lisa Lanigan; Jillynne Zeller; Derek Cissell; Monica Metea; Eric Adams; Mikayla Higgins; Kwi Hye Kim; Ewa Budzynski; Lin Yang; Ye Liu; Mark Butt; et al. (Molecular Therapy: Methods & Clinical Development, 2022)
Recent studies in non-human primates administered recombinant adeno-associated viruses (rAAVs) have shown lesions in the dorsal root ganglia (DRG) of unknown pathogenesis. In this study, rAAV9s manufactured using different purification methods alongside a non-expressing Null AAV9 vector was administered to groups of cynomolgus monkeys followed by neuropathological evaluation after 4 weeks. Lesions, including neuronal degeneration, increased cellularity, and nerve fiber degeneration, were observed in the DRG, regardless of purification methods. Animals did not develop any neurological signs throughout the study, and there was no loss of function observed in neuro-electrophysiological endpoints or clear effects on intraepidermal nerve fiber density. However, magnetic resonance imaging (MRI) of animals with axonopathy showed an increase in short tau inversion recovery (STIR) intensity and decrease in fractional anisotropy. In animals administered the Null AAV9 vector, DRG lesions were not observed despite vector DNA being detected in the DRG at levels equivalent to or greater than rAAV9-treated animals. This study further supports that DRG toxicity is associated with transgene overexpression in DRGs, with particular sensitivity at the lumbar and lumbosacral level. The data from this study also showed that the nerve fiber degeneration did not correlate with any functional effect on nerve conduction but was detectable by MRI.